Źródła myśli księdza Aleksandra Zienkiewicza o człowieku i społeczeństwie - Ignacy Dec (Wrocławski Przegląd Teologiczny)
The author presents sources of the anthropology of Fr Aleksander Zienkiewicz. These sources have been divided into the following groups: main personal patterns (his family and people he met during his study period at the Priests Seminary in Pinsk (Belarus today); Holy Scripture, teaching of the Church and great theologians; follow philosophers, psychologists and educators; the next group consists of men of science and culture (scholars, poets and writers); finally – saints and national heroes. The author concludes that God and man was the main theme of the teaching of Fr Zienkiewicz. Both the image of God and of man, in his teaching were based on the Holy Scripture, the classical philosophy, theology, psychology, pedagogy and classical literature.